(untitled) (Ameghiniana, 2013)
Well preserved Podagrosiceras spp. have been found in the Puchenquia malarguensis assemblage at the quasi-type locality in Neuquén, establishing their age as latest Aalenian to earliest Bajocian (Concava-Discites Zones). P. athleticum Maubeuge et Lambert, type species, is a microconch with lateral lappets; the septal suture is as in Hammatoceratinae. P. sp. nov. is described from the same assemblage. "Podagrosiceratidae" Maubeuge et Lambert, 1955, without status because of missing diagnosis or description, are intermediate between Hammatoceratinae and Erycitinae. They may require validatian at the subfamily level if diversity can be demonstrated.